One-year developmental changes in motor coordination and tennis skills in 10-12-year-old male and female tennis players - Waldzinski, T.; Waldzinska, E.; Durzynska, A.; Niespodzinski, B.; Mieszkowski, J.; Kochanowicz, A. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background To date, no longitudinal studies of quarterly changes have been conducted on the differences in the development of motor coordination between boys and girls in relation to changes in their tennis skills level. Therefore, the aim of the study was to assess the development of motor coordination of 10-12-year-old tennis players over the course of 1 year, in the light of changes in tennis skills preparation.